Afro-brazilian religions in the religion market and the attack by neo-pentecosal churches (Tempo e Argumento, 2011)
The purpose of this article is to discuss the evasion of members of a group of Afro-Brazilian religions and the attacks suffered by candomble and umbanda, mainly by neo-Pentecostal churches. The discussion addresses the following issue: which are the most significant weaknesses of Afro-Brazilian religions that are leading to the evasion of their members and to constant and aggressive attacks by the neo-Pentecostal? For that purpose, it is necessary to introduce, historicize and contextualize religion in Brazil, evidencing the status of Catholicism as the official religion since the Discovery until the creation of the Republic, and its decline when religious freedom and pluralism was implemented. In order to reach their goal, this study is based on texts by authors that are familiar with the discussion at hand and with religion sociology.
Keywords: afro-brazilian religions; candomble; umbanda; neo-pentecostal churches